An experimental approach to the study of interpersonal violence in Northeastern Patagonia (Argentina), during the late Holocene - Gordón, Florencia (2012)
This paper incorporates an experimental approach to the study of violence patterns in Northeastern Patagonia (Argentina) during the late Holocene. The underlying hypothesis considers a close association between socio-ecologic alterations during the Medieval Climatic Anomaly (MCA) (ca. 1150-600 years BP; Stine, 1994, 2000) and a probable increase in conflict levels. In order to test this hypothesis, human skulls (n = 986) were analyzed for bone lesions, discriminating late bone lesions, such as those produced by metal tools. The experimental approach used swine (Sus scrofa domestica) skulls, as proxies for human skulls, and incorporated original sabers. From this discriminating analysis, it can be inferred that no significant increase in violence signs were recorded until the first stages of Hispanic-indigenous contact (first half of 17th century). These findings emphasize the need for a revision of the implications of the dynamics of human populations in Northeastern Patagonia during the late Holocene.